A Longitudinal analysis of the Porterian paradigm utilization in Brazil - Simone Sehnem; Fábio Lazzarotti; Rodrigo Bandeira-de-Mello (BBR: Brazilian Business Review)
The purpose of this article is to investigate to what extent Michael Porter's ideas keep attracting the interest of Brazilian researchers vis-à-vis other possibilities. In this research, we conceptualize Porter's paradigm by the the following elements: strategic groups, generic strategies, model of the five forces and value chain. Weanalyzed conferece communications to EnANPAD¿s, from 1998 to 2008, and to 3Es, from 2003to 2007. The results indicate a decline in the use of the porterian paradigm as the main axis of research in strategy. The generic strategies and the model of five forces are the elements of Porter's paradigm most employed, while the concepts of strategic groups and value chain are the ones that received less attention by researchers. The analysis of methodology and purpose of comunications indicates that the "porterian life" in Brazil was characterized by the acritical use of its concepts in order to describe the reality of the strategy in Brazil. There are no evidences of consistent and systematic attempts to test or adapt the porterian paradigm for the Brazilian context. And results indicate no evidences that this trend will be reversed.